Polos e áreas de influência: uma proposta de regionalização econômica para o estado do Paraná - Gotardo, Daiane Marani (2015)
Regional inequalities do not occur only among large Brazilian regions, but are also common feature among the States in the same macro-region, thus, it is common to talk about regional differences even within the same State. The State of Paraná occupies a prominent position on the socio-economic development compared to other Brazilian States; however, it shows great regional inequalities. Considering this situation of high inequality, regional analyzes are important because the differences among the regions are the main issues on regional economic studies. Such analyzes are usually carried out considering the traditional division of space established by the Instituto Brasileiro de Geografia e Estatística (IBGE) (Brazilian Institute of Geography and Statistics). However, the use of this regionalization can be inadequate to distinguish one region to any other, which must necessarily be taken into account in the design of economic development strategies. In this sense, this study makes a proposal for regionalization in strictly economic terms for the State of Paraná for ensuring the consistency of analyzes, actions, measures, and uses of economic policy instruments suggested by regional planners. This regionalization takes place considering the identification of economic centers and their areas of influence, so that the measurement of the interactions intensity among these points is essential to the delimitation of economic regions. The economic centers are set to meso-regional level and the State's municipalities are the units for analysis. The analysis is operationalized by the Gravitational Model, which uses "mass" and distance to calculate the interaction degree between two points in space. Through the Gravitational Model, respecting the contiguity among the areas and using the experience of other studies, economic regions could be delimited to Paraná State, which showed to be different from traditional regional sections.